The ‘The Mark of the Beast’: Showing Rudyard Kipling’s Intrinsic Manner on the Short Story - Rizka Istama, Nanda; Ugi Sutikno, Eka; Tri, Haliza; Ardelia, Sita (JEDLISH : Journal Of Education and English Language Teaching, 2024)
The narrative manner, plot, characterization, and background cannot be separated from the short story; they help readers understand the author’s intentions. This research aims to determine the short story’s plot, characterization, and background. The method used is a qualitative descriptive approach. The data collection model is implemented in three ways: reading, listening, and taking notes. Data analysis is done by reducing, presenting, and drawing conclusions. The short story “The Mark of The Beast” tells the journey of the main character, Fleete, who is involved in supernatural events after insulting a religious temple in India. This character also displays character transformation and the roles of supporting characters such as Strickland and Others. The dominant theme is the conflict between spiritual and worldly forces and the spiritual journey of individuals in facing the consequences of their actions. Overall, the short story “The Mark of the Beast” shows the depth, complexity, and fear that exist in this work. By understanding the plot, characterization, and background in this story, readers can explore the meaning of this story more deeply and appreciate the messages conveyed by the author about life, local customs, and spiritual powers that exist in the story.